THE ZEN CLOWN IKKYU A CROSS CULTURAL STUDY IF A SYMBOL OF DISORDER - Olson, Carl (Journal of Dharma, 1999)
Taking into consideration the rigorous discipline, strict monastic regulations, and arduous daily scheduled of a Zen Buddhist monk, it would appear to be self-contradictory to assert that a monk could achieve enlightenment and then faithfully patronize local brothels. It would also appear to be self-contradictory to drink tea in a monastery and sake at a local wineshop, to carry a human skull on a long bamboo pole through the streets and to wander the mountainous terrain of Japan in solitude, and to become head of a leading temple in the twilight years of one’s life and during the same period to become involved in an illicit love affair. These apparent contradictions characterize the life of Ikkyu Sojun (1394-1481), a monk and poet of the Rinzai sect. Ikkyu’s behaviour was often bizarre, obscene and outrageous even for an ordinary individual, let alone a Zen monk. His appearance, humorous antics, obscene behaviour, and unusual literary compositions closely resemble the nature of a clown.